2019
DOI: 10.1177/1077699019850096
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasive Effect of Journalistic Storytelling: Experiments on the Portrayal of Exemplars in the News

Abstract: This study aims to deepen our understanding of the persuasive effects of exemplars in the news by addressing the role of character depiction. Exemplification theory and narrative persuasion research are integrated to shed light on the psychological mechanisms mediating the persuasive effect. Two replicative field experiments (N = 389) were conducted manipulating the depiction of the character within a print news article in three factor levels (no exemplification, external view, and internal view). Regardless o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Building on such insights, recent experimental studies by Bas and Grabe have highlighted the importance of "emotion-provoking personalization" of news, showing that including the emotional testimonies of ordinary people in investigative stories limited knowledge gaps between higher and lower education groups (e.g. Bas and Grabe, 2015) and encourages political participation (Bas & Grabe, 2016; see also Grabe et al, 2017;Oschatz, Emde-Lachmund & Klimmt, 2019). Similarly, experimental studies of stories about mass violence in Africa have demonstrated that "story personification"or stories focused on the plight of a single victimcontribute to elevating emotional responses and thereby "bolster support for intervention" (Maier, Slovic & Mayorga, 2016, p. 1012.…”
Section: News Audiences and Emotionmentioning
confidence: 99%
“…Building on such insights, recent experimental studies by Bas and Grabe have highlighted the importance of "emotion-provoking personalization" of news, showing that including the emotional testimonies of ordinary people in investigative stories limited knowledge gaps between higher and lower education groups (e.g. Bas and Grabe, 2015) and encourages political participation (Bas & Grabe, 2016; see also Grabe et al, 2017;Oschatz, Emde-Lachmund & Klimmt, 2019). Similarly, experimental studies of stories about mass violence in Africa have demonstrated that "story personification"or stories focused on the plight of a single victimcontribute to elevating emotional responses and thereby "bolster support for intervention" (Maier, Slovic & Mayorga, 2016, p. 1012.…”
Section: News Audiences and Emotionmentioning
confidence: 99%
“…Moreover, although it appears that the inclusion of characters' perspectives is engaging and persuasive, less is known about how these perspectives are to be represented to achieve maximal impact. A recent study found no differences in engagement and persuasion between news articles including the internal perspectives of news characters and news articles including their external perspectives (Oschatz et al, 2019). In this study, internal perspectives were established by the inclusion of thoughts and emotions.…”
Section: Literary Techniques In Journalismmentioning
confidence: 68%
“…During the COVID-19 pandemic media sources commonly presented both news focusing on statistics and news focusing on people's personal experience with COVID-19. This presentation of personal stories of people who suffer from COVID-19, or the personal accounts of people who cared for COVID-patients, is an often-used strategy in journalism, called exemplification (Oschatz et al, 2021;Kramer & Peter, 2020). In exemplification, a news item reports on a single case with regards to a certain topic, with a focus on personal experience and vivid details (Zillman, 1999).…”
Section: Factual Vs Personal Newsmentioning
confidence: 99%
“…Most work in media science so far has examined the outcomes of engaging with different types of news (e.g., Oliver et al, 2012;Oschatz et al, 2021), manipulated motivationally-relevant aspects of news (e.g., Knobloch-Westerwick et al, 2005;Grizzard et al, 2017) or measured motivations to engage with news in general (e.g., Hoffner et al, 2009;Mothes, et al 2018; see for an overview: Knoblich-Westerwick, et al, 2020). The present study will focus on the expectations that people have about the impact of reading unique negative news items, in order to examine how these motives predict choice behavior.…”
Section: Distinct Motives To Engage With Negative Newsmentioning
confidence: 99%